Safety of inhaled nitric oxide withdrawal in severe chronic pulmonary hypertension - Gregorio Miguel Pérez‐Peñate; Gabriel Juliá‐Serdá; Helena Galván‐Fernández; Desireé Alemán‐Segura; Fernando León‐Marrero; Antonio Garcia‐Quintana; Iñigo Rúa‐Fernández deLarrinoa; José Ramón Ortega‐Trujillo; Miguel Ángel Gómez‐Sánchez (Pulmonary Circulation, 2024)
Abstract Inhaled nitric oxide (iNO) is a potent and selective pulmonary vasodilator with a safety concern due to rebound pulmonary hypertension (PH) associated with its withdrawal. We report short‐term pulsed iNO in patients with severe pulmonary arterial hypertension (PAH) and nonoperable chronic thromboembolic PH (nCTEPH). This is a retrospective analysis of 33 patients: 22 with PAH and 11 with nCTEPH. We assessed hemodynamic, echocardiographic, and other noninvasive variables to evaluate safety and efficacy of iNO. We performed an iNO withdrawal test during right heart catheterization and after 3 days of iNO treatment. iNO significantly improved all variables examined in 22 patients with PAH and 11 with nCTEPH. Two patterns of response were observed after sudden iNO withdrawal. Twenty‐nine patients (88%) showed minimal hemodynamic, oxygenation and clinical changes. Four patients (12%) had a reduction in cardiac index ≥20% and PaO2 ≥ 5%, three patients did not show clinical deterioration, and one patient developed hemodynamic collapse that needed iNO administration. This retrospective study suggests that short‐term iNO improves hemodynamics and clinical conditions in some patients with PAH an nCTPEH. However, pulsed iNO withdrawal PH rebound could be a serious concern in these patients. Given the lack of evidence, we do not recommend the use of pulsed iNO in the treatment of patients with chronic PH.